Kuliah Kerja Nyata Berbasis Masjid Kelompok 37 UINFAS Angkatan-III Di Masjid At-Taqwa Desa Jayakarta - Mohammad Hakamul Ulum Attamimi; Muhammad Farhan; Sugeng Riyanto; Laila Tri Oktavianti; Belindah Salsa Bela; Okta Yana Satri; Reni Hayati; Arrum Peksi Malachah; Novi Arazak; Fiki Bela Anggraini (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research discusses the activities of Community Service Program (KKN) Group 37, aimed at enhancing the welfare of the communities in Dusun II and Dusun III through various social and educational programs. The method used is active participation in community activities, such as teaching Quranic lessons, mosque cleanliness programs, planting family medicinal plants (TOGA) and vegetables, and study guidance at the mosque. The results indicate that these programs successfully improved the skills and knowledge of the community, strengthened relationships among residents, and created a healthier and cleaner environment. Program evaluation was conducted through surveys and discussions with residents, showing positive responses to the KKN initiatives. This research underscores the importance of student involvement in community development and provides insights into implementing similar programs in the future.